Analisis Nilai Tambah Dan Finansial Pengolahan Tepung Menjadi Pie Kelor Bali - Kaleka, Marten Umbu; Budiasa, I Wayan; Gede Ustriyana, I Nyoman (JURNAL MANAJEMEN AGRIBISNIS; Vol 10 No 1 (2022): Jurnal Manajemen AgribisnisDO - 10.24843/JMA.2022.v10.i01.p01, 2022)
The development of the agricultural sector needs to diversify agricultural products into a product, namely Moringa pie which has added value, in addition to serving a large market it is necessary to patent a product by establishing a processing plant which is the existence of the Moringa pie product. The development of the moringa pie agro-industry needs to be studied in terms of added value and finance. This research was conducted at PT Bali Agro Investama, Penyaringan Village, Mendoyo District, Jembrana Regency. The location selection was done by using purposive sampling method based on certain considerations. The data analysis used is a quantitative method, namely added value and investment criteria. The results showed that (1) the added value of the moringa pie processing was classified as high, namely Rp. 697,725.42 with a value added ratio of 37.03%, (2) The results of financial analysis such as Break Even Points (pieces) were 355,043 (pieces) and Break. Sales Even Point (rupiah) IDR 710,086,624.03, Net Present Value IDR 3,402,121,393.90 without financing or with bank financing, Net B / C 3.12 without financing if using bank financing Net B / C value 3.70 . Furthermore, the Internal Rate of Return obtained a return rate of 78.43% without financing, if using bank financing the IRR value was 89.36% and the short Payback Period was 20.37 months without financing, and with bank financing to 23.04 months. (3) The results of the sensitivity analysis of the 15% sales discount obtained a Net Present Value of Rp. 159,977,262.90 without financing or bank financing, Net B / C value of 1.10 without financing, and with bank financing of 1.13. Internal Rate of Return 27.28% without financing and with bank financing of 27.59%. While the sensitivity of operating costs increased by 15%, obtaining a Net Present Value of Rp. 914,489,765.54 without financing or bank financing, Net B / C of 1.57 without financing and with bank financing of 1.73, the Internal Rate of Return obtained a value. 39.35% without financing and with bank financing 41.52%. The results of these calculations meet the investment eligibility criteria so that the moringa pie processing business is feasible.